Model predictive current control for four‐switch three‐phase rectifiers in balanced grids. Issue 1 (1st January 2017) - Liu, Yong‐Chao; Ge, Xinglai; Tang, Qidi; Deng, Zhixian; Gou, Bin
Abstract : A model predictive current control scheme with dc‐link capacitor voltages fluctuation suppression for the four‐switch three‐phase rectifier (FSTPR) in balanced grids is presented. The proposed control scheme is a type of the finite‐control‐set model predictive control scheme and is based on the discrete‐time model of the system. From this model, the values of input currents and dc‐link capacitor voltages are predicted for all switching states of the FSTPR. On the basis of a predefined cost function, the switching state, which minimises the errors between input currents and their references as well as the difference between two dc‐link capacitor voltages at the next sampling instant, is selected. Simulation results are presented to confirm the effectiveness of the proposed control scheme.